2004
DOI: 10.1128/aem.70.8.4582-4587.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Arsenic Accumulation in Engineered Bacterial Cells Expressing ArsR

Abstract: The metalloregulatory protein ArsR, which offers high affinity and selectivity toward arsenite, was overexpressed in Escherichia coli in an attempt to increase the bioaccumulation of arsenic. Overproduction of ArsR resulted in elevated levels of arsenite bioaccumulation but also a severe reduction in cell growth. Incorporation of an elastin-like polypeptide as the fusion partner to ArsR (ELP153AR) improved cell growth by twofold without compromising the ability to accumulate arsenite. Resting cells overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
74
4
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(84 citation statements)
references
References 31 publications
2
74
4
4
Order By: Relevance
“…The level of enhancement is consistent with the observed increase in As(III) uptake due to GlpF overexpression (Table 2), reflecting the additive effect on accumulation of coexpression of fMT and GlpF. The final level of 8.1 mol/g (dry cell weight [DCW]) is three times higher than levels recently reported for other engineered E. coli strains (16,30,32).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The level of enhancement is consistent with the observed increase in As(III) uptake due to GlpF overexpression (Table 2), reflecting the additive effect on accumulation of coexpression of fMT and GlpF. The final level of 8.1 mol/g (dry cell weight [DCW]) is three times higher than levels recently reported for other engineered E. coli strains (16,30,32).…”
supporting
confidence: 71%
“…Although metal-chelating peptides such as metallothionein (MT) have been overexpressed in microorganisms for enhanced accumulation of Cd and Cu, almost all such peptides lack specificity for As (1,2,20,29,31,34,35). Specific arsenic accumulation has been reported by utilizing the metalloregulatory protein ArsR (16) or phytochelatins (13,21,32). However, enzymatic synthesis and the availability of precursors such as glutathione and ␥-glutamylcysteine require actively growing cells and limit the utility of the metal-chelating ArsR and phytochelatins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to isolate glyco-polypeptides using the interaction between the capture molecule and the sugar group [86] (Figure 8). It has also been shown that ELPs fused to an appropriate fusion partner can bind to heavy metals such as mercury [87], arsenic [88] or cadmium [89,90], and facilitate the rapid isolation of these toxic metal contaminants.…”
Section: Applications Of Elp-based Protein Purification-as the Princimentioning
confidence: 99%
“…To recycle the ELP-MerR fusion protein for reuse, resuspend ELP aggregates with ice-cold TB7.4M, preferably in the same volume added in Step 20. 24 are also used (see Fig. 2b).…”
mentioning
confidence: 99%